Нариси з історії львівської астрономії - Апуневич, С.; Новосядлий, Б. (Праці наукового товариства ім. Шевченка, 2011)
The history of astronomical science development on the terrains of Western Ukraine appears to be long interesting and complex just like the history of this land The history of Lviv astronomy resembles the history of the city which had been raised on the cross roads of cultures and civilizations and appears as the perplexed lace of cultural civilizational and unseldom personal links We have made an attempt to illuminate some of the aspects of the history of astronomical science in Lviv exactly as a system of links between persons and ideas with continuity in time The essay embraces the earliest stages of this history starting from rst references to astronomy on the terrains of Western Ukraine (XVth century) the period of foundation of Lviv Observatory is described in detail as well as the dramatic fate of Lviv astronomy during XIX century The reestablishment of Astronomical observatory at its contemporary location is treated separately.